Induced Mutagenesis in Yellow Flowering Marigold with Colchicine in Hydrogen Peroxide - Susrama, I Gede Ketut; Yuliadhi, Ketut Ayu (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 2 (2020): ATBES, 2020)
Marigold flower has many benefits in many aspects of life in Bali Island (Indonesia) including often used in religious ceremonial activities. For controlling plant pests and diseases, marigold is planted on the sidelines or on the edge of a land as an attractant crop to invite natural enemies and marigold also can produce certain substance which can reduce the incidence of nematode. In inducing mutagenesis in this research, the seeds of marigold were soaked in solution of colchicine with hydrogen peroxide as its solvent. The results of this research indicated that the treatments caused the formation of chlorophyll mutant and an increase in the length of flower diameter. Both the control and treated plant samples were attacked by leaf miner, giant land snail, virus-like disease and botrytis flower blight disease.